Quantitative determination of an effective component of Fumaria parviflora Lam. - F Khalighi-Sigaroodi; D Yazdani; M Taghizadeh; Sh Rezazadeh (Institue of Medicinal Plants, ACECR, 2005)
Background: 7 species of the annual plants of genus Fumaria, grow in Iran. Fumaria officinalis is the medicinal species, which is used as a cholagogue. F. officinalis is not found in Iran but F. parviflora is used instead, in folk medicine. It is thought to be a expectorant, diuretic, diaphoretic, gastric tonic, blood purifier, bitter tonic, laxative, intoxicant, astringent, sedative and has favorable effects on skin complaints. Objective: The aim of this study was quantitative determination of the effective component (fumaric acid) of Fumaria parviflora Lam. Methods: Medicinal parts of F. parviflora are aerial parts. The aerial parts of F. parviflora in the flowering stage were collected in July 2003 from Halejerd. Powdered plant was extracted with petroleum ether, chloroform, acetone and methanol using a soxhlet extractor. Fumaric acid content was analyzed by HPLC. Results: Fumaric acid content of the dried plant was determined to be about 0.93% w/w.